Existence results for a multipoint boundary value problem of nonlinear sequential Hadamard fractional differential equations - Ahmad,Bashir (Universidad de La Frontera. Departamento de Matemática y Estadística., 2021)
ABSTRACT In this paper, existence and uniqueness results are established for a nonlinear sequential Hadamard fractional differential equation with multi-point boundary conditions, via Banach and Krasnosel'skiĭ's fixed point theorems and Leray-Schauder nonlinear alternative. An example illustrating the existence of a unique solution is also constructed.